Extra and intracellular laccase titers of xylophagic bacteria isolated from adult termite (Acta Scientiarum. Technology, 2021)
Laccase is an important enzyme in terms of its versatile applicability, but its commercial use is limited by factors such as high production cost, low activity and/or stability under given conditions. The objective of this study was to screen xylophagic bacteria isolated from termites for the production of extracellular and intracellular laccases. Six laccase-positive strains were isolated, namely CA, A3, A5, A6, A7 and A8. They were molecularly identified by sequence analysis of 16S rRNA and classified under the genera Bacillus (A7, A8, CA) and Pseudomonas (A3, A5, A6). Laccase was produced by these bacterial isolates by submerged fermentation and was optimized at 37Â°C, pH 5.5, 6.2 and 7.0, with agitation and 0.5 mM guaiacol (as carbon source). Laccase activity was determined by measuring the oxidation of guaiacol and ABTS (2,21-azino bis[3-ethylbenzthiazoline-6-sulfonate]). Strain A5 produced extracellular laccase titers ranging from 123 to 168 U ml-1. Guaiacol was identified as a better substrate for the quantification of laccase. In conclusion, bacteria harboring the gut of termites can produce extracellular laccase with activity at medium to moderate acidity.